(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Access to the right to food is one of the most important basic Human Rights in the world. The significance of food is equal for every human being. Therefore the government at the national international level have made several attempts and initiated several schemes and programs so that every individual will enjoy his or her right to food in a true spirit. however there are various challenges and he shows associated while exercising the right to food. These issues are specially faced by the people who belong to the vulnerable and disadvantaged sections of the society. To reduce this problem, this paper has made an attempt to understand the real issues and hurdles in realisation of access to write to food as a human right. This paper also focuses on pragmatic implementation of various laws and schemes at the national level from socio-legal perspective.